Development of Small-Medium Industry in Urban Kampong to Realize a Sustainable Creative Economy Area - Siti Sujatini; Euis Puspita D; Dwi Dinariana; Henni Henni; Ari Wijaya (Research Synergy Foundation, 2023)
The concept of the creative economy has emerged recently, one of which is the emergence of small and medium industries (IKM) in urban kampong. The creative economy is the driving force for the nation's economy, so its existence needs to be managed and developed. The emergence of the IKM creative economy concept is inseparable from the cultural characteristics of rural communities, which have characteristics of